Readiness Level of Bottled Drinking Water Production Facilities in Meeting Good Processed Food Production Requirements in the Aceh and Bogor Regions - Sarah, Shanty; Zain, Ufaizah (Indonesian Health Journal, 2024)
Bottled drinking water (AMDK) is a food product consumed by all levels of society in Indonesia and produced in large quantities. This widespread consumption has resulted in AMDK being categorized as a high-risk food. To maintain product safety and quality, the government issued several regulations governing producers in producing AMDK products, including the obligation to implement Good Processed Food Production Methods (CPPOB). However, not all AMDK producers have and fulfill the requirements for implementing CPPOB. This research aims to analyze the distribution of AMDK producers and the level of readiness of AMDK production facilities in the Aceh and Bogor regions. This research also aims to map the distribution of AMDK production facilities and compare the CPPOB values in the two regions. The research was carried out using a survey method to collect data regarding the distribution of AMDK producers and the level of readiness of production facilities in the Aceh and Bogor regions. The data collected was then analyzed to create a map of the distribution of AMDK production facilities and calculate and compare CPPOB values in the two regions. The analysis results show that the CPPOB value in the Bogor region is higher (76.56%) than in the Aceh region (50%). This difference is caused by the different scale characteristics of the AMDK production business in the two regions. Several clauses cause the CPPOB value of AMDK production facilities to be D and C, including those related to process control and prevention of cross-contamination, raw materials, packaging, and final products; personnel training; employee facilities, and personnel cleanliness; in-house testing laboratory; as well as building construction and layout.